Workplace physical exercises, obesity anthropometric indexes, blood pressure and static muscle strength (Acta Scientiarum. Health Sciences, 2014)
http//dx.doi.org/10.4025/actascihealthsci.v36i1.14982Current analysis compares anthropometric indexes of obesity, blood pressure and static muscle strength among workers who exercised or did not exercise themselves on the workplace. Three hundred and fifty-four workers, of whom 178 did not perform any physical exercises and 176 who did, were evaluated by means of a query on their participation in workplace exercises during the last 30 days. Their systolic (SBP) and diastolic blood pressure (DBP) was measured; height, body mass and waist circumference (WC) were taken; four static muscle strength tests (right and left handgrip strength, scapular strength and lumbar strength) were performed. The Shapiro Wilk test revealed asymmetry in the data presented as median and interquartile variance. Mann-Whitney test was used to compare data between the two groups. Results did not reveal any difference for body mass index (BMI), WC, SBP, DBP and mean blood pressure (MBP) between the groups. However, greater performance was an asset for all participants in workplace exercises for all static strength tests. There is evidence that workers who performed workplace exercises may increase muscle strength without any changes in BMI, WC and blood pressure.